THE DEVELOPMENT OF PROFESSIONAL LEARNING COMMUNITY OF DONMOON SCHOOL (SUWANNASARAJBAMRUNG) BY USING BENCHMARKING WITH LAMPLAIMATPATTANA SCHOOL - (Viriya Warayu), วิริยะ วรายุ; (Anucha Kornpuang), อนุชา กอนพ่วง (Journal of Education and Innovation, 2018)
This research aimed at developing professional learning community of Donmoon School (Suwannasarajbamrung) by using benchmarking with Lamplaimatpattana School. The procedure composed of four steps: 1) Planning, including the establishment of a team to make the benchmarking, determination of benchmarking. The pair set benchmarking and the collection of data. 2) Analysis Data, including data analysis for finding the distance. 3) Integration, including the report on benchmarking and goals to the team. 4) Action, include plan implementation, implementation of the plan into action and repeat calibration. The results were as follows: 1. Planning found that a team with the appointment of the researcher comparable performance in this research and to educate the participants about the progress of the team benchmarking (Benchmarking) to develop professional learning community (Professional Learning Community : PLC) in the benchmarking section of this research include the development of professional learning community. Partner in the implementation of benchmarking in this research is Donmoon School (Suwannasarajbamrung) by using benchmarking with Lamplaimatpattana School and are planning to collect data by interviewing the person responsible for the process development of professional learning community of both schools. 2. Analysis Data found that the state of development. The process of professional learning communities Lamplaimatpattana School higher information than Donmoon School (Suwannasaraj-bamrung) all integration. 3. Integration found that should have taken a community development process professional learning environments. Because each element has a relationship together. The development will be carried out simultaneously unable to perform only one component elements and has set the goal of developing a more comparable with the results of the Lamplaimatpattana School. To reduce the spread of the process of developing a professional learning community of Donmoon School (Suwannasarajbamrung) with Lamplaimatpattana School. 4. Action Plan found that the conceptual framework of the implementation of the development process of professional learning communities as a guide to plan and carry out calibration has been performed repeatedly. When completed the implementation of the action plan. The result is displayed the implementation process of developing a professional learning community, all the elements of Donmoon School (Suwannasarajbamrung) information increased by close to Lamplaimatpattana School.